2006
DOI: 10.1029/2005gl025053
|View full text |Cite
|
Sign up to set email alerts
|

Shear‐wave splitting beneath the southwestern Kurile arc and northeastern Japan arc: A new insight into mantle return flow

Abstract: [1] Shear-wave splitting in the southwestern part of the Kurile arc and the northeastern (NE) Japan arc is investigated using the waveforms from local earthquakes. For both arcs observed shear-wave splitting shows clear evidence for a striking rotation of fast direction across the arc, suggesting the different feature of anisotropy between the fore-arc and back-arc sides. Trench-parallel fast directions are observed in the fore-arc side, which is consistent with the anisotropy expected from the deformation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
92
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 27 publications
10
92
0
Order By: Relevance
“…The 16°angle is close to the 15°standard deviation angle of each station computed in section 6.1. The near-surface polarization in the western part of Figure 13b correlates well with observations of the shear wave polarization at greater depth [Okada et al, 1995;Nakajima and Hasegawa, 2004;Nakajima et al, 2006], but this agreement does not hold in the regions further east.…”
Section: Shear Wave Splitting and The Direction Of The Plate Motionsupporting
confidence: 74%
“…The 16°angle is close to the 15°standard deviation angle of each station computed in section 6.1. The near-surface polarization in the western part of Figure 13b correlates well with observations of the shear wave polarization at greater depth [Okada et al, 1995;Nakajima and Hasegawa, 2004;Nakajima et al, 2006], but this agreement does not hold in the regions further east.…”
Section: Shear Wave Splitting and The Direction Of The Plate Motionsupporting
confidence: 74%
“…In NE Japan, a clear pattern on the polarization direction of shear-wave splitting was found (Nakajima et al, 2006). Trench-parallel and trench-normal polarization directions were found at the fore-arc side and back-arc side of the volcanic front, respectively.…”
Section: Resultsmentioning
confidence: 88%
“…These reflect the changes in allocation of the arc-trench system before and after the opening of the Japan Sea; the latter was NE-SW (oblique to the present NE Japan arc) before the opening, and NNE-SSW (parallel to the present NE Japan arc) after the opening until the present (Otufuji et al 1985;Ohki et al 1993;Yoshida et al 1999b). The present-day mantle structure, including the low velocity and mantle anisotropy structures Nakajima et al 2006b), is principally parallel to the present arc-trench system, although there are some mantle heterogeneities in the areas of SW Honshu and NE Honshu bordered by the TTL. Therefore, it is likely that the along-arc spatial variation of the Quaternary lava chemistry is mainly affected by the overlying lithosphere, and the most plausible candidate for affecting this appears to be the lower crustal melts, which can contribute to both the origin of the basement granitoids and to the Quaternary lavas.…”
Section: Role Of the Heterogeneous Lower Crustmentioning
confidence: 99%
“…Shearwave splitting analyses reveal that the low-V and low-Q zones in the mantle wedge show strong seismic anisotropies (Okada et al 1995;, Nakajima et al 2006b). Anisotropic bodies are revealed in the crust, mantle wedge and the subducting Pacific slab (Hall et al 2000;Nakajima et al 2006b;Wang & Zhao 2008;Huang et al 2010). have clearly shown that the azimuth in the forearc region is trench-parallel, whereas in the back-arc region the azimuth is trench-normal (Fig.…”
Section: Along-arc Mantle Heterogeneitymentioning
confidence: 99%